Hemorrhagic complications after stroke treatment with intravenous thrombolysis despite use of direct oral anticoagulants: an observational study - Kleeberg, Antonia; Ringleb, Peter A.; Huber, Ioana; Jesser, Jessica; Möhlenbruch, Markus Alfred; Purrucker, Jan (Therapeutic advances in neurological disorders, 2024)
Background: For patients experiencing ischemic stroke despite receiving therapy with direct oral anticoagulants (DOAC) and without endovascular treatment options, therapeutic prospects are currently dismal. Current guidelines recommend intravenous thrombolysis (IVT) only for patients who have received DOAC in very restricted settings, as an increased risk of bleeding is suspected. However, recent retrospective observational studies suggest that IVT is safe despite DOAC pretreatment. - Objectives: To provide further evidence that IVT despite previous DOAC treatment is not associated with an increased risk of bleeding. - Design: Observational retrospective study. - Methods: Demographic, clinical, and radiological data of patients who received IVT (+/− endovascular thrombectomy) despite DOAC pretreatment between June 2021 and January 2024 were analyzed using descriptive statistics, including DOAC plasma concentration at admission. Secondary intracranial hemorrhages and functional outcomes at 3 months were assessed. Since 2023, patients have been treated according to a modified local standard operating procedure at our hospital, allowing for IVT despite DOAC pretreatment regardless of DOAC plasma levels or the use of reversal agents. - Results: Of 1821 patients treated with acute recanalization procedures during the study period, N = 35 had received IVT with (18) or without (17) additional endovascular therapy. Among these patients with a wide age range (42-97 years) and DOAC plasma concentrations up to 369 ng/ml, only one developed symptomatic intracranial hemorrhage. A favorable outcome (modified Rankin scale score 0-2) after 3 months was observed in 57% (20) of the patients. - Conclusion: IVT despite direct oral anticoagulation seems to be safe, even at advanced age and high DOAC plasma levels.